A Study on Challenges and Opportunities of Health Tourism in India with Reference to Public Health - Ghosh , Malay (International Journal of Psychosocial Rehabilitation, 2020)
The tourism business is not restricted to hotels, restaurants, sightseeing, & adventure businesses. The meaning of it goes much beyond this then. When it comes to health tourism, it is not a new word. It has its roots in ancient history in India. The health tourism industry has two components. Health and (ii). Tourism, which is growing at a very rapid pace. The medical industry or health tourism is considered to be one of the fastest-growing sectors in the world, consisting of promising sectors of medical and health tourism. This paper highlights the scope, growth, and challenges of medical tourism in India. From traditional value-based medical systems to modern medical infrastructure development. The cost component, availability of resources, govt. guidelines, infrastructure development, and research in medical science are some of the determining factors for the growth of medical tourism. This paper also focuses on various challenges and opportunities available in India related to this sector.